The acute effect of dynamic vs. proprioceptive neuromuscular facilitation stretching on sprint and jump performance - Malek, N. F. A.; Nadzalan, A M.; Tan, K.; Azmi, A. M. N.; Vasanthi, R. K.; Pavlovic, R.; Badau, D.; Badau, A. (Journal of Functional Morphology and Kinesiology, 2024)
Participating in sports has been shown to promote overall wellness and, at the same time, reduce health risks. As more people are participating in sports, competitions have increased, and every aspect of the game has been focused by coaches and athletes in order to improve performance. One of these aspects is the warm-up session. The purpose of this study was to investigate the acute effect of a dynamic warm-up versus a proprioceptive neuromuscular facilitation (PNF) warm-up on the sprint and jump performance of recreationally active men. Thirty (n = 30) males were randomly assigned to undergo three sessions of different warm-up types, 72 h apart, involving either proprioceptive neuromuscular facilitation (PNF), dynamic stretching (DS), or no stretching session (control). The PNF and dynamic modes of stretching improved vertical jump performance, F (2.58) = 5.49, p = 0.046, to a certain extent (mean + 3.32% vs. control, p = 0.002 for dynamic and mean + 1.53% vs. control, p = 0.048 for PNF stretching). Dynamic stretching is best used to get a better vertical jump height. Sprint performance was also increased to a greater extent following the stretching session, F (2.58) = 5.60, p = 0.01. Sprint time was +1.05% faster vs. the control, with a value of p = 0.002 after dynamic stretching, while PNF stretching demonstrated a sprint time of +0.35% vs. the control, with a value of p = 0.049. Dynamic stretching showed a better sprint performance and also vertical jump height performance in this study. PNF and dynamic stretching prove to be equally efficacious in flexibility conditioning depending on the type of movement involved. This type of stretching should be utilized to help preserve or improve the performance output of physical activity, especially in sprinting and jumping events.